Development of water reuse: a global review with the focus on India - Kirti Goyal (IWA Publishing, 2021)
The availability of freshwater is evolving as a serious threat to the living community throughout the world due to rapid industrialization, urbanization, and rising population. The depletion of groundwater due to excessive water withdrawal and reduced recharge and pollution of the water sources also contributes to this water crisis. The rising pressure on water supplies encourages the use of treated wastewater as an alternative resource. In this study, a global outlook of the developments in water reuse is presented with a focus on the Indian scenario. It can be observed that though there is a scope for water reuse in India owing to the generation of a high volume of wastewater, it is often squandered due to limited research and guidance, and unreliable institutional framework. It is suggested that the reuse of wastewater requires the development of an integrated approach considering all the factors related to technical feasibility, financial viability, and social acceptance together with a guiding management structure that may augment the existing water supplies. HIGHLIGHTS Provides an overview of factors influencing water reuse throughout the world.; Discusses regional challenges with regard to the implementation of water reuse schemes worldwide.; Provides insight to the existing reuse scenario and future opportunities in India.;